2012
DOI: 10.1017/s1368980012003473
|View full text |Cite
|
Sign up to set email alerts
|

Trends in excess of weight, underweight and adiposity among Spanish children from 2004 to 2010: the Cuenca Study

Abstract: Objective: To examine the trends in BMI and adiposity among schoolchildren from Cuenca, Spain, during 2004Spain, during -2010. Design: Two methodologically comparable surveys were carried out in 2004 and 2010. Setting: Primary schools in Cuenca, a province in the middle of Spain. Subjects: All schoolchildren aged 8-11 years, belonging to 4th and 5th grades from twenty schools in the Province of Cuenca, were invited to participate in both cross-sectional studies. Weight, height and body fat percentage (BF%) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0
13

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 30 publications
4
23
0
13
Order By: Relevance
“…Internationally, recent research has indicated some levelling off in the overweight prevalence in girls (2) and boys (3) . However, a reduction in overweight prevalence has been noted in girls (3) .…”
mentioning
confidence: 99%
“…Internationally, recent research has indicated some levelling off in the overweight prevalence in girls (2) and boys (3) . However, a reduction in overweight prevalence has been noted in girls (3) .…”
mentioning
confidence: 99%
“…España ha sido el país donde más estudios se han realizado, con un total de seis (2,4,10,19,25,34), el segundo país ha sido Inglaterra, con un total de 3 estudios (3,30,31), con 2 intervenciones está Alemania (5,26), Francia (13,29), Chile (18,32,35) Tabla I. Referencias de los estudios científicos seleccionados (n = 28) y Estados Unidos (1,33) y, por último, con una intervención se encuentran Nueva Zelanda (6), Turquía (27), Islandia (24), Suecia (28), Sur África (23), México (36), Georgia (7) y la India (22). En relación al contexto donde se desarrollan las intervenciones, en la tabla II se puede observar que 8 de ellas se desarrollaron en horario extraescolar, 1 fuera del entorno escolar y 14 en horario escolar.…”
Section: Diseño/tipo De Estudiounclassified
“…Un total de 101.193 escolares fueron incluidos en los diversos trabajos analizados (1)(2)(3)(4)(5)(6)(7)10,13,18,19,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)33,34,36).…”
Section: Población/características De La Muestraunclassified
See 2 more Smart Citations